Mobile Phones and Development in Africa Does the Evidence Meet the Hype? - Aker, Jenny C.; Cariolle, Joël (Palgrave Studies in Agricultural Economics and Food Policy, 2023)
XXI, 174 p. 23 illus., 22 illus. in color.